Statistical Modelling of Robotic Manipulators - Machado, J. A. Tenreiro (2016)
The article presents a new approach to the analysis and design of robotic manipulators. The novel feature resides on a non-standard formulation to the modelling problem. usually, system descriptions are based on a set of differential equations which, due to their nature, lead to very precise results and strategies but require laborious camputations. This motivates the need of alternative models based on other methematical concepts. The proposed statistical method gives clear guidelines towards the robot kinematic and dynamic optimsation. Furthermore, the results point out strutural characteristics of the trajectory planning algorithm as well as ideal-actuator properties.